Towards Excellence in Engineering Education - Ouahada, Khmaies (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Acquiring knowledge is a life-long process; we constantly need to keep abreast of developments and progress in science and other disciplines. Embracing a scholarship of teaching and learning (SoTL) means practicing constant self-reflection, involving evaluation of the academic career and the ways in which strategies are designed to examine, interpret, and share learning about teaching. This practice not only yields benefits to the lecturer but also enriches the scholarly community in the discipline. In general, SoTL is regarded as a vibrant practice of ongoing self-criticism and sharing, which results in accumulated teaching experiences for teachers, students, and the teaching community at large. This book is a contribution from authors sharing their experiences, how their teaching portfolios reflect their personal development as teachers, and how their teaching experiences are embedded in the scholarship of teaching and learning.